Perspectiva de género aplicada en investigaciones periciales de femicidio a través de entrevistas a víctimas indirectas: un estudio de caso (Tema Central) - Guillén Pachacama, Stefany (2025)
This article explores the importance of including interviews with secondary victims in the development of gender-context forensic assessments in femicide cases, as a key tool for information gathering. The objective is to identify the gender-based motives that drive perpetrators to kill women because of their gender, using testimony from close relatives such as children, siblings, and the victim’s mother, whose proximity allows them to provide valuable insights into the dynamics of the case. The inclusion of this methodological tool is recommended due to the persistent difficulty in prosecuting these crimes, as justice system actors often limit their forensic analysis to the violent act itself, neglecting the broader context. Additionally, the article proposes the use of the Feminist Ecological Model as a theoretical framework to analyze how different forms of violence operate simultaneously. The aim is to demonstrate the relevance of a gender perspective not only in the research design, but also in the organization and analysis of findings, ensuring that victims receive truth, justice, and reparation.